2022
DOI: 10.3390/children9020153
|View full text |Cite
|
Sign up to set email alerts
|

Screening, Diagnosis and Early Intervention in Autism Spectrum Disorders

Abstract: The increment of prevalence is among the most important changes that have taken place in recent years with regard to Autism Spectrum Disorder (ASD); in the 1970s and 1980s of the 20th century, the prevalence of ASD was estimated to be 4/10,000 [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 49 publications
0
8
0
1
Order By: Relevance
“…1 Our study adds to a growing body of literature highlighting the limitations of common pediatric developmental and behavioral assessment tools for non-White populations. [36][37][38] This study, however, has several limitations. Similar to many longitudinal data sets with multiple waves of data collection, the ECLS-B has missing data.…”
Section: Discussionmentioning
confidence: 96%
“…1 Our study adds to a growing body of literature highlighting the limitations of common pediatric developmental and behavioral assessment tools for non-White populations. [36][37][38] This study, however, has several limitations. Similar to many longitudinal data sets with multiple waves of data collection, the ECLS-B has missing data.…”
Section: Discussionmentioning
confidence: 96%
“…There could be many explanations for the absence of effects. We suggest that the main priority in relevant research should be to identify which treatment works best and for whom [ 72 , 73 ]. It is not yet clear which characteristics of a child and family may affect the success of an intervention.…”
Section: Discussionmentioning
confidence: 99%
“…In our review, the age range of the participants was found to be 24–132 months. Although there have been a limited number studies examining the influence of age of therapy initiation on outcomes, research has shown that the sooner an intervention takes place, the higher the impact on the altered brain circuity of children with ASDs, resulting in positive outcomes [ 72 , 73 ]. In addition, the predictive value of cognitive ability at pre-treatment on participants’ performance is not yet clear [ 21 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When should preventive measures begin? Early diagnosis of ASD is crucial for the correct prevention of oral health being undertaken at early as possible (55)(56)(57). Diagnosing autism during pregnancy is a possibility, particularly for women at risk (58,59), yet dental assistance and counseling should be promoted to parents as soon as the possibility of autism spectrum disorder has been forecast (60,61).…”
Section: Concerns and Suggestionsmentioning
confidence: 99%